If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 75 = -5a + -25 Reorder the terms: 75 = -25 + -5a Solving 75 = -25 + -5a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '5a' to each side of the equation. 75 + 5a = -25 + -5a + 5a Combine like terms: -5a + 5a = 0 75 + 5a = -25 + 0 75 + 5a = -25 Add '-75' to each side of the equation. 75 + -75 + 5a = -25 + -75 Combine like terms: 75 + -75 = 0 0 + 5a = -25 + -75 5a = -25 + -75 Combine like terms: -25 + -75 = -100 5a = -100 Divide each side by '5'. a = -20 Simplifying a = -20
| 23x-11y=7 | | 2(6)+3(5+3)= | | (2x^2)-1=0 | | -34=83-9x | | 65+0.06c=48+0.10c | | 2-7(4-6x)=0 | | 5x+3=-3x+19 | | -3x-13=17 | | -(b-4b)=8b-b | | 3x-1=-32 | | 2+3(4+1)= | | 16=r+20 | | 7m-34=6m-4(-7-8m) | | 3-9(8x+2)=4 | | (3x^2)x^5= | | 11x+70=-128 | | 4.7x+4.1x=-15.84 | | 3x-9y=21y | | 6.8x=11.5 | | 14x-4=18x-7 | | 7(6)+3-5(6)= | | -54=-15-3x | | 48+4y-20=17y-12-5y | | 2z-4-z=2 | | n-13=-33 | | -14x^2-49=0 | | 6x-7=8x+15 | | 3(0)+2(0)+7= | | -25=-9+x | | 56-11x=199 | | y=3x^2+10x | | 55-12x=139 |